Switching majors – into and out of economics. Issue 3 (3rd July 2019) - Emerson, Tisha L. N.; McGoldrick, KimMarie
Abstract: Using student transcripts from six institutions over a 23-year timespan, the authors investigate the movement of students into and out of the economics major. Considerable movement between majors occurs with 83 percent of economics graduates switching in after their first principles course. These eventual majors come from a variety of sources, but primarily from business, engineering, science and maths. In an absolute sense, weaker students (as measured by cumulative GPA) switch into economics. However, students appear to move to disciplines of relative academic strength (as indicated by relative grades). While females from other majors are less likely to switch into economics, traditionally underrepresented minorities are largely attracted to economics from other disciplines at similar (or higher) rates to which they persist in originally declared majors.